Implementation of Problem Based Learning (PBL) Model in Indonesian Language Teaching for Grade IV Primary School Students - Amalia Tri Ariani; Amanda Diva Fidiati; Dianita Ayu Permata; Andika Hilda Rizki; Wahyu Sukartiningsih; Zulfin Rachma Mufidah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
study aims to analyze the application of the Problem Based Learning (PBL) learning model in teaching the Indonesian Language in class IV SDN Lidah Kulon 1 Surabaya. The background of this research departs from the low interest and attention of students to Indonesian language learning, especially in speaking skills, caused by the dominant use od the lecture method. The research method used is qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of this study show that the application of the Problem-Based Learning (PBL) model helps increase students’ active involvement, strengthen critical thinking, and improve learning outcomes following the Criteria for Achieving Learning Objectives (KKTP). With proper planning, implementation, and evaluation, the problem-based learning (PBL) model proved effective in creating a more interactive and meaningful learning atmosphere for students.Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality Education